Ecosystem services and hydroelectricity in Central America: modelling service flows with fuzzy logic and expert knowledge - Locatelli, Bruno; Imbach, Pablo; Vignola, Raffaele; Metzger, M.J.; Hidalgo, E. J. L. (Springer, 2011)
Because ecosystem services are generally not produced and used in the same place, their assessment should consider the flows of services from ecosystems to users. These flows depend on the characteristics and spatial distribution of ecosystems and users, the spatial relationships between them, and the presence of filters or barriers between ecosystems and users. The objective of this paper is to map the ecosystem services provided to the Costa Rican and Nicaraguan hydroelectric sectors, which are crucial sectors for national sustainable development and depend directly on hydrological ecosystem services. The paper presents an approach for modelling the flows of multiple services from diverse ecosystems to diverse users through different kinds of filters in a landscape. The approach uses expert knowledge and fuzzy numbers to handle uncertainties. The analyses for Costa Rica and Nicaragua show how the approach helps identify priority areas for the conservation and restoration of forests for the services they provide to the hydroelectric sector. As such, it is a useful tool for defining spatially targeted policies for the conservation of ecosystem services and for involving the users of ecosystem services in ecosystem management.